Analisis Pengaruh Bank Terhadap Kinerja Bank Pengkreditan Rakyat di Provinsi Kepulauan Bangka Belitung - Aprilia, Elsa Cherri (CV ODIS, 2025)
The substantial annual decrease in the number of People’s Credit Banks (BPR) drives this study. The ongoing drop is attributable to the consolidation or merging of BPR and in part to the revocation of business licenses. The purpose of this study is to assess and scrutinize the financial ratios pertaining to the performance of banks providing credit to individuals. This study utilizes quantitative data. The utilized data is secondary, sourced from the Indonesia Financial Services Authority website and the relevant People’s Credit Banks. The panel data regression was used as the analytical method, implementing the Fixed Effect Model (FEM) approach through E-Views 9. The results indicated that the Loan to Deposit Ratio, Operating Costs, and Operating Income all had a positive and significant impact on Return on Asset. Moreover, Non-Performing Loan Net had a positive an insignificant effect on Return On Asset. Simultaneously, Loan to Deposit Ratio, Operating Costs and Operating Income, and Non- Performing Loan Net had a positive and significant effect on Return on Asset.